PENGARUH AIR REBUSAN DAUN SALAM TERHADAP PENURUNAN KADAR ASAM URAT PADA PENDERITA ASAM URAT DI DESA WONOSARI KECAMATAN SENORI KABUPATEN TUBAN - Kurniawan, Vendi Eko (WELL BEING, 2020)
(THE EFFECT OF BROKEN WATER LEAVES ON THE REDUCTION OF URIC ACID LEVELS IN URIC ACID SUFFERERS IN WONOSARI VILLAGE, SENORI DISTRICT, TUBAN DISTRICT) Vendi Eko Kurniawan1, Zeny Fatmawati2, Diah Ayu Meilinda3, 1,2,3STIKes Husada Jombang Email : vendi.awan@gmail.com ABSTRACT Uric acid is the result of purine metabolism in the body contained in the blood and urine. There are several ways to overcome uric acid, one of therapy herbal bay leaf. The purpose of this study to the influence of the water decoction of the leaves to decrease the levels of uric acid in patients with gout in the Village of Wonosari Kecamatan Senori Tuban Regency. The design used in this research is pre-experimental approach with one-group pretest-posttest design. This research was conducted in the Village of Wonosari Kecamatan Senori Tuban on December 15-23 May 2020. Population and sample in this study were all patients with gout in the Village of Wonosari Kecamatan Senori Tuban Regency a number of 37 people by using a sampling technique total sampling. While the instrument used is a tool checks the uric acid and checklist. Data analysis by using T-Test. The results of this research note that the average uric acid levels before the administration of water decoction of bay leaf is 7,549 mg/dl. While the average levels of uric acid after administration of water decoction of bay leaf is 5,616 mg/dl. Data analysis using T-Test obtained ρ = 0.000 < α = 0.05 so H1 is accepted meaning that there is the effect of water decoction of the leaves to decrease the levels of uric acid in patients with gout. Efforts of health workers so that uric acid levels decreased is to provide IEC about the use of water decoction of bay leaf as a treatment alternative in patients with gout. Keywords: boiling water, bay leaf, decrease uric acid levels.